A buffered impact damper for multi-degree-of-freedom structural control. - Li, Kuinian (Earthquake engineering & structural dynamics.)
The results of an experimental investigation into the use of a buffered impact damper for controlling the dynamic response of an MDOF (multi-degree-of-freedom) structure are presented in this paper. Free and forced vibration tests of a three-DOF test structure equipped with a buffered impact damper are performed to evaluate the resulting damping effect and impact characteristics. The effect of damper parameters, such as clearance, and excitation type on the performance of the impact damper is also investigated. The performance of the buffered impact damper is compared with that of an equivalent conventional rigid impact damper. It is found that the buffered impact damper not only significantly reduces the peak contact force and the associated accelerations and noise generated by collisions but can also substantially enhance the damping effect over a wide range of frequencies, encompassing the natural frequencies of the test structure.